2022
DOI: 10.1097/mao.0000000000003778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Global Pandemic on Adult and Pediatric Cochlear Implantation across the United States

Abstract: ObjectiveTo characterize the effect of the COVID-19 pandemic on national cochlear implantation utilization by age using inclusive cochlear implantation data from two manufacturers between 2015 and 2020.Study DesignAnalysis of prospectively registered consecutive patient data from two major cochlear implant (CI) manufacturers in the United States.PatientsChildren or adults who received CIs.InterventionsCochlear implantation.Main Outcome MeasuresAnnual implantation utilization by age.ResultsA total of 46,804 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Nassiri et al (4) reported a 43% increase in CI procedures at high-volume cochlear implant centers from 2015 to 2020. In the largest cohort to date, data from two CI manufacturers reported a similar increase from 2015 to 2019 of 49% (9). Although previous studies have provided rates of change over an entire study period, we additionally report an AAGR.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Nassiri et al (4) reported a 43% increase in CI procedures at high-volume cochlear implant centers from 2015 to 2020. In the largest cohort to date, data from two CI manufacturers reported a similar increase from 2015 to 2019 of 49% (9). Although previous studies have provided rates of change over an entire study period, we additionally report an AAGR.…”
Section: Discussionmentioning
confidence: 86%
“…Active-duty service members are preferentially treated at military treatment facilities, although this population rarely receives cochlear implants and we do not believe this difference in populations to be an important factor. In addition, this study includes the years before the COVID-19 pandemic, and this likely influenced CI trends (9). Future work in this area looks to project changing practice trends within otology, identify and limit barriers to implantation, specifically as they relate to the general otolaryngologist.…”
Section: Discussionmentioning
confidence: 99%
“…Durability is important particularly in the extremes of the age spectrum. The recall also came at a particularly unfortunate time where a global pandemic strained the health care system and resulted in an average 13% drop in implant utilization, worse in patients older than 80 years (21). Octogenarians are particularly vulnerable because of their higher risk of poor outcomes with COVID infection, difficulties communicating with masks, social isolation, more significant hearing loss, less awareness, and less likelihood of seeking care (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this study presents data through 2019, before the start of the COVID-19 pandemic, which had a significant impact on the rates of CI performed in the US (23). Although CI practices are recovering from the effects of the pandemic, rates of CI may not have recovered to the pre-pandemic numbers described above.…”
Section: Discussionmentioning
confidence: 99%